Mining claim at Rock Creek, Alaska, approximately 1901. - Hegg, Eric A., 1867-1948 (1901)
Probably Rock Creek located 7 miles northwest of Nome on the Seward Peninsula. Shows two men working with sluicing operation. Caption on image: "No. 1 A Rock Creek." Original image in Hegg Album 27, page 42. Original photograph by Eric A. Hegg 1767; copied by Webster and Stevens 74.A Nome Gold Rush.